2021
DOI: 10.1177/15280837211032078
|View full text |Cite
|
Sign up to set email alerts
|

A novel algorithm for significantly increasing the fiber volume fraction in the reconstruction model with large fiber aspect ratio

Abstract: Geometric reconstruction is an important precondition for the computational micromechanics analysis of chopped fiber reinforced composites. When fiber aspect ratio increases, the maximum fiber volume fraction in reconstruction model reduces rapidly because of jamming limit, which greatly limits the application of reconstruction methods. A novel algorithm is proposed to significantly increase the fiber volume fraction in the reconstruction model of the chopped fiber reinforced composites with large fiber aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The runtime for the unidirectional case is extremely small, as expected. Indeed, even random sequential addition (RSA) methods [14][15][16][17] are able to generate unidirectional states at high filler fraction. Non-aligned fiber-orientation states are more difficult to handle, and this is where most traditional algorithms have their limitations.…”
Section: Results Of Varying Fiber-length Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The runtime for the unidirectional case is extremely small, as expected. Indeed, even random sequential addition (RSA) methods [14][15][16][17] are able to generate unidirectional states at high filler fraction. Non-aligned fiber-orientation states are more difficult to handle, and this is where most traditional algorithms have their limitations.…”
Section: Results Of Varying Fiber-length Parametersmentioning
confidence: 99%
“…Simple algorithms based on random sequential addition (RSA) [10,11] fail to produce microstructures with industrial volume fraction and moderate fiber aspectratio, i.e., the quotient of fiber length and diameter, and this limitation is intrinsic [12,13]. Therefore, a number of improved RSA methods was introduced [14][15][16][17]. Sequential deposition [18,19], flexible fiber based [20,21] and collec-tive re-arrangement algorithms [22][23][24] are more successful when it comes to reaching the desired volume fractions.…”
Section: State Of the Artmentioning
confidence: 99%
“…Results indicated that the cross-sectional morphology of fibers with high fiber volume fractions tended to be more rectangular under varying compaction loads, thus providing valuable insights for the prediction of composite material performance. Li et al 14 put forward a novel algorithm for enhancing the fiber volume fraction in the reconstruction model of short cut fiber reinforced composites with large aspect ratios. This algorithm enables the pre-design and control of fiber orientation and length distribution in the reconstruction model, resulting in a significant increase in fiber volume fraction in the range of 50∼200 fiber aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 However, numerous studies have found that the fibers are distributed at random. 7,8,9,10 Many efficient methods for achieving the random fiber distributions of the RVEs that correspond to the crosssections of unidirectional FRC have been developed by researchers. Buryachenko et al 11 elaborated the background notions and definitions of the random fiber distributions, and provide a method for obtaining the fiber centroid coordinates of using a random distribution method based on a digital image processing technology.…”
Section: Introductionmentioning
confidence: 99%